Potential of cavalcade, Centrosema pascuorum, leaves for controlling Meloidogyne javanica and quantification of active phytochemicals - Beesa, N.; Chinnasri, B.; Sasnarukkit, A.; Dethoup, T.; Jindapunnapat, K.; Kiriga, A.W.; Saikai, K.; Haukeland, Solveig; Coyne, D. (Brill, 2023)
The legume cavalcade, Centrosema pascuorum, is used extensively as a cover crop and as a component of conservation agriculture systems. It is also an attractive rotation or cover crop for the management of root-knot nematodes (RKN; Meloidogyne spp.) as it is a non-host. RKN are persistent pests that are well known to be difficult to control. However, the mechanisms governing the non-host status of cavalcade is unknown. The current study established that cavalcade leaves are toxic to RKN as either aqueous extracts or soil amendments. Bioassays conducted using Meloidogyne javanica showed that a 90% concentration of aqueous extract derived from 1-month-old cavalcade leaves (89 mg crude extract ml−1) suppressed nematode hatch (82.9%) and killed infective second-stage juveniles of M. javanica (85.3%). Soil amendments with 1% (w/w) of 1-month-old cavalcade leaves (0.99 mg crude extract g−1 soil) also provided effective control of M. javanica in the glasshouse on okra. One-month-old leaves appeared more effective than 2- or 3-month-old leaves. The soil amendments had no adverse phytotoxic effect on okra seed germination. Our study demonstrates the potential for using cavalcade leaves or extracts to manage RKN. This may be due to the nematicidal activity of the various compounds in the leaves, such as flavonoids, phenols and terpenoids, which should be further assessed.